Combined Liver and Lung Transplantation With Extended Normothermic Lung Preservation in a Patient With End‐Stage Emphysema Complicated by Drug‐Induced Acute Liver Failure. Issue 10 (6th August 2014) - Ceulemans, L. J.; Monbaliu, D.; Verslype, C.; van der Merwe, S.; Laleman, W.; Vos, R.; Neyrinck, A.; Van Veer, H.; De Leyn, P.; Nevens, F.; Pirenne, J.; Verleden, G.; et al.
<x xml:space="preserve">Abstract</x> Isolated lung transplantation (LuTx) and liver transplantation are established treatments for irreversible lung and liver failure. Combined liver and lung transplantation (cLiLuTx) is a less common, but approved therapy of combined organ failure, mostly applied in patients suffering from progressive cystic fibrosis and advanced liver disease. We report a patient who was listed for LuTx due to end‐stage chronic obstructive pulmonary disease and who developed drug‐induced acute hepatic failure. The only therapeutic option was hyper‐urgent cLiLuTx. To correct the poor coagulation in order to reduce the per‐operative risk of bleeding, the liver was transplanted first. In anticipation of the longer lung preservation time, cold flushed lungs were preserved on a portable lung perfusion device for ex vivo normothermic perfusion for 11 h 15 min, transplanted sequentially off‐pump, and reperfused after a total ex vivo time of 13 h 32 min and 16 h for the first and second lung, respectively. Ten months later, the patient is doing well and no rejection occurred. Normothermic ex vivo lung perfusion may help to prolong preservation time, facilitating long‐distance transport and combined organ transplantation.